PERLAWANAN NAHDLATUL ULAMA (NU) TERHADAP PEMERINTAHAN ORDE BARU MELALUI WACANA POLITIK - Arif Rohman (Jurnal Penelitian Humaniora, 2004)
Abstract This study intends to describe the process of Nahdatul Ulama (NU) critical faction resistance against hegemony by new Order nation through political discourse. Some data can be collected through in-depth interview and through document study. Theinterview was done toward six people elite of NU, while the document study originated from the clipping from Java Post scripts, and there NU magazines; Aula, Pesantren and Bangkit. Eventually some data especially based on the further interview result is processed by qualitative analysis and it be collected through document study si processed by contend analysis. The final inference obtained is, that during the period of one decade before upcoming president Soeharto falling, have become the conflict relation between NU critical faction against New Order nation through the political discourse. So, the correlation between both is in more antagonist striped, among other things assigned by the appearance of NU critical faction against New Order nation. That is that resistanceof political discourse directing of the from of ‘counter-hegemony’ from on part against ‘hegemony’ from the  others. Keywords: Nahdatul Ulama, new order, conflict, and political discourse